EFFECTIVITY OF CANBAT HERB FROM PT. MEDDIA HERBAL TO Aeromonas hydrophilla INFECTION ON NILE FISH (Oreochromis sp.) - andri kurniawan; Reza Hermawan; ahmad fahrul syarif (Journal of Aquatropica Asia, 2022)
Tilapia (Oreochromis sp.) is a consumption fish inhabiting freshwater and likeability by society. Tilapia’s benefits can attract breeders to cultivate in mass-producing with very high market demand. Every mistake that occurs in aquaculture activities is usually the feeding management which can cause various problems, such as damage to water quality that can trigger growth—diseases, including Motile Aeromonas Septicemia (MAS) caused by Aeromonas hydrophila. The use of Canbat assumed there are contain some antioxidants that can be used as immunostimulators to increase the survival of tilapia. This research aimed to find out the concentration of Canbat product PT. Meddia herbal is effective for the treatment of tilapia (Oreochromis sp.) infected by Aeromonas hydrophila bacteria. The method used in this research was experimental. The size of tilapia used is 10-11 cm with a density of 10 fish/container. The treatment doses used were P1 (40 ppm), P2 (60 ppm), P3 (80 ppm), Positive control (Amoxicillin), and Negative control (0 ppm), with 2-hour immersion. The parameters observed were clinical symptoms, fish survival, fish response to feed, and absolute weight growth. The results indicated that herbal Canbat with concentration (80 ppm) was effective in treating tilapia infected with Aeromonas hydrophila bacteria; it produces the fastest recovery of clinical symptoms on the 12th day and the highest survival rate of 90%.